Layer-by-layer combination of laser powder bed fusion (LPBF) and femtosecond laser surface machining of fabricated stainless steel components. (October 2018) - Ghosh, Abhi; Wang, Xianglong; Kietzig, Anne-Marie; Brochu, Mathieu
Graphical abstract: Highlights: Layer-by-layer in-situ surface treatment with femtosecond laser was shown for laser powder bed fusion produced SS316L. Accumulated fluence profile model was used to optimize the ablation parameters towards groove-free machined side-walls. Continuous stretch of side-walls with uniform sub-micrometer scale surface texture were extended over multiple layers. Side-wall roughness of the machined multiple layers was comparable or lower than conventionally post-processed parts. Abstract: Post-processing techniques for surface machining of laser powder bed fusion (LPBF) fabricated parts offer limited access to internal surfaces in complex shapes, precision surfacing, side-wall morphology, and material removal rates, thereby considerably limiting their applicability. In this work, a two-step fabrication involving the initial fusion of a powder layer in a LPBF set-up followed by the selective ablation of layer contours by rastering normally incident femtosecond laser pulses, is repeated for every layer of the built. For 1   k H z repetition rate, pulse fluence of 6.7   J / c m 2 and super-Gaussian beam of shape factor 16, an experimentally obtained groove-free surface on laser machined walls was correlated with scan speeds when the pulse accumulated fluence distribution profile was horizontally flat or constant. Increasing the line overlap in raster scans did not yield any noticeable change in the machined wall surface. Groove-free surfaces, uniformly textured with sub-micrometer spaced laser-induced periodic surface structures (LIPSS), were successfully extended over side-walls of several unidirectionally machined consecutive layers. Ultimately, laser machined multi-layered LPBF parts possessing average side-wall roughness of R t = 4.7 ± 1 μ m and side-wall taper angle of as low as ∼ 3 ° ± 1 ° were fabricated.